2013
DOI: 10.1063/1.4824774
|View full text |Cite
|
Sign up to set email alerts
|

Electron-hole pair generation in SiC high-temperature alpha particle detectors

Abstract: Abstract-We demonstrate alpha-particle detection in an n-type 4H-SiC Schottky diode detector up to an unprecedented temperature of 500 °C using an Am-241 disc source. The measured spectra were used to calculate the electronhole pair creation energy in 4H-SiC and its non-bandgap contribution, which are both found to decrease with increasing temperature. The full width at half maximum (FWHM) of the measured alpha-energy peaks was found to increase exponentially with temperature due to an exponential increase of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 10 publications
0
10
1
Order By: Relevance
“…This change in the energy value is less than it is predicted in the work of Garcia et al [6] where for the temperature range of 23 • C-400 • C, 2.7% change in the energy to create an electron-hole pair is prevised. From the fitted σ-value of the Gauss function a 38% increase in the full width at half maximum was established which was caused by the elevating leakage and thermal noises of the semiconductor diode at higher temperatures.…”
Section: Resultscontrasting
confidence: 45%
See 1 more Smart Citation
“…This change in the energy value is less than it is predicted in the work of Garcia et al [6] where for the temperature range of 23 • C-400 • C, 2.7% change in the energy to create an electron-hole pair is prevised. From the fitted σ-value of the Gauss function a 38% increase in the full width at half maximum was established which was caused by the elevating leakage and thermal noises of the semiconductor diode at higher temperatures.…”
Section: Resultscontrasting
confidence: 45%
“…In the work the effect of the external temperature on the signal of the diodes, the different thermal noises and current values were carefully examined. Garcia et al [6] investigated the change in electron-hole pair generation energy as a function of the temperature with alpha particle irradiated SiC detectors, they explained the effect of the generation energy on peak broadening and energy shift in the recorded energy spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Note that the range of the Xe ions at 1217 MeV in SiC is about . For the average electronhole pair creation energy in SiC, a value of was used, which is an average between the recently published experimental values of [17] and [18]. For modeling the avalanche multiplication, an anisotropic impact ionization model that is especially developed and calibrated for 4H-SiC power devices [19] has been implemented in Silvaco TCAD tools, and was used in this work.…”
Section: Tcad Simulations and Discussionmentioning
confidence: 99%
“…Pyroprocessing is performed in a molten salt which is maintained at about 500°C, a temperature where Si and other common roomtemperature detectors will fail because Si behaves as a metal instead of a semiconductor due to its relatively low bandgap. We have recently shown that detectors made from 4H-SiC, a wide-bandgap semiconductor, can measure alpha particle energy spectra up to 500°C with a 3 mm diameter circular active area [4]. Detectors such as these may be able to survive in the nuclear fuel treatment facility tanks.…”
Section: Introductionmentioning
confidence: 99%